(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There was an increasing number of studies which systematically analyzing the antecedents and outcomes of the public-private partnership approach in the public sector. Lamentably, there was a few researchers focus on studying on the impact of public-private partnership on the tourism infrastructure and tourism service innovation as a mediating variable in local government. The public-private partnership has been applied by the government and the private sector in Sinjai Regency in improving the tourism service innovation and development of tourism infrastructure destination. Likewise, this research has a primary purpose to measure the impact of public-private partnership on the development of tourism infrastructure destination and tourism service innovation as a mediating variable in Sinjai Regency, South Sulawesi Province. The research population consists of 512 people, which included the Tourism and Culture staff at Sinjai Regency, legislative, local community, restaurant and café, and the private organizations that actively involvedin providing tourism infrastructure destination. The research sample was selected201 respondent base on the statistic methods and procedure to determine the research sample. We used 50 percent of the research population that is consisted of 123 male and 78 female for each characteristic of the population. Data were gaining through questionnaires and analyzed by using Structural Equation Modelling through SPSS and AMOS software windows version 24. The researchers proposed three hypotheses and the results of SEM analysis showed that all hypotheses were supported. We recommend that the public-private partnership models have benefits of building the tourism service innovation and sustainable development of the tourism destination infrastructure in local government.